2014
DOI: 10.1113/jphysiol.2014.271213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of detraining on the temporal expression of positive and negative angioregulatory proteins in skeletal muscle of mice

Abstract: Key pointsr Skeletal muscle capillary regression is associated with elevated thrombospondin-1 and vascular endothelial growth factor protein expression with detraining.r Vascular endothelial growth factor and nucleolin responses to acute exercise are blunted in the triceps surae muscles following exercise training. In the plantaris and soleus muscles, this blunted response persists up to 28 days after cessation of training.r Effects of detraining on skeletal muscle microvascular density appears to be similar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 47 publications
3
26
2
Order By: Relevance
“…detraining), and that at this timeframe, muscle capillarity had already reverted back to pretraining levels (despite the presistent elevation in muscle VEGF) [74]. This was a robust response seen in several muscles of the distal hindlimb (i.e., soleus, gastrocnemius, plantaris) ( Table 1), each representing varying degrees of oxidative and glycolytic potential [74]. Consistent with this observation, two prior studies involving exercise training in rats, have also found detraining-induced capillary regression whilst basal muscle VEGF expression is elevated [46,65] (Table 1).…”
Section: Capillary Regression Correlates Better To Changes In Tsp-1 Tmentioning
confidence: 87%
See 1 more Smart Citation
“…detraining), and that at this timeframe, muscle capillarity had already reverted back to pretraining levels (despite the presistent elevation in muscle VEGF) [74]. This was a robust response seen in several muscles of the distal hindlimb (i.e., soleus, gastrocnemius, plantaris) ( Table 1), each representing varying degrees of oxidative and glycolytic potential [74]. Consistent with this observation, two prior studies involving exercise training in rats, have also found detraining-induced capillary regression whilst basal muscle VEGF expression is elevated [46,65] (Table 1).…”
Section: Capillary Regression Correlates Better To Changes In Tsp-1 Tmentioning
confidence: 87%
“…These studies provide the seemingly provocative observation that physiologically mediated capillary regression is not dependent on the withdrawal of VEGF. Two of aforementioned studies, Huttemann, Lee and Malek [46] and Olenich et al [74], report the additional finding of elevated skeletal muscle expression of TSP-1, a potent negative angiogenic regulator. The temporal correlation of TSP-1 with detraining-induced capillary regression suggests that TSP-1, or perhaps more generally negative angiogenic regulators, may be the key determinant in initiating and regulating capillary regression.…”
Section: Capillary Regression Correlates Better To Changes In Tsp-1 Tmentioning
confidence: 97%
“…In addition to the complexities of VEGF involvement (Wagner 2011), the pro-and antiangiogenic responses to short-term exercise and withdrawal have only recently been reported (Hellsten & Hoier 2014, Olenich et al 2014), but parallel studies on blood flow have not been conducted.…”
Section: Biochemical Responses Induced By Elevated Shear Stressmentioning
confidence: 99%
“…1979), and more recently in exercise‐trained mice where a complex pattern of pro‐ and antiangiogenic factor changes was observed (Olenich et al . 2014). The speed of vascular regression is important as it may influence the progression of impaired function associated with, for example, bed rest and the use of angiotherapies.…”
mentioning
confidence: 99%
See 1 more Smart Citation